PENGARUH SAAT PEMANGKASAN TUNAS LATERAL DAN DOSIS PUPUK NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI KERITING (Capsicum annum L.) - Susanto, Hermawan; Pamungkas, Djoko Heru; Zamroni, Zamroni (Universitas Sarjanawiyata Tamansiswa, 2019)
This study aims to determine the effect of NPK fertilizer dosage and when Â trimming lateral shoots to growth and yield of curly chili plants. This research was conducted in Kukap, Poncosari, Srandakan, Bantul, Yogyakarta with a height of 20 masl, regusol soil type, pH between 5.3 - 6.8 and average temperature 260 C - 380 C , and is held from September to December 2018. This study was conducted using a 2 x 2 + 1 control factorial experiment compiled in a Complete Randomized Block Design (RAKL). The treatment consists of two factors, the first factor is the treatment of pruning. The second factor is the dose of NPK fertilizer. Each treatment was repeated three times. The results of the analysis showed that there were interactions between the two factors in the outcome variable, where the control treatment of pruning at 7 days and 14 days and the fertilizer dose of 1.25 tons/ha gave the highest fruit weight yield. Giving fertilizer doses and pruning times showed no significant effect on plant growth and quality